Statistical view to development Lithuania: Prospects of competitiveness in the enlarged European union - Ginevičius, Romualdas (Journal of Business Economics and Management, 2004)
The aim of the paper is to present a statistical view to Lithuanian development tendencies and to highlight specific features of country's economic structure. Statistical approach grounded on theoretical elaborations of consistent patterns of transition countries’ development should lead to concretization of state economic policy in field of defining of development directions.First Published Online: 14 Oct 2010